Afforestation, reforestation and new challenges from COVID-19: Thirty-three recommendations to support civil society organizations (CSOs). (1st June 2021) - Mohan, Midhun; Rue, Hayden A.; Bajaj, Shaurya; Galgamuwa, G.A. Pabodha; Adrah, Esmaeel; Aghai, Matthew Mehdi; Broadbent, Eben North; Khadamkar, Omkar; Sasmito, Sigit D.; Roise, Joseph; Doaemo, Willie; Cardil, Adrian
Abstract: Afforestation/reforestation (A/R) programs spearheaded by Civil Society Organizations (CSOs) play a significant role in reaching global climate policy targets and helping low-income nations meet the United Nations (UN) Sustainable Development Goals (SDGs). However, these organizations face unprecedented challenges due to the COVID-19 pandemic. Consequently, these challenges affect their ability to address issues associated with deforestation and forest degradation in a timely manner. We discuss the influence COVID-19 can have on previous, present and future A/R initiatives, in particular, the ones led by International Non-governmental Organizations (INGOs). We provide thirty-three recommendations for exploring underlying deforestation patterns and optimizing forest policy reforms to support forest cover expansion during the pandemic. The recommendations are classified into four groups - i) curbing deforestation and improving A/R, ii) protecting the environment and mitigating climate change, iii) enhancing socio-economic conditions, and iv) amending policy and law enforcement practices. Graphical abstract: Image 1 Highlights: Civil Society Organizations promote afforestation/reforestation (A/R) endeavors. A/R programs help meet the United Nations Sustainable Development Goals. COVID-19 can alter the trends of deforestation and forest degradation. Increased budget cuts cause new challenges for A/R. Remotely sensed data can aid in optimizing resource allocation.